Implementasi Konsep â€œJourney To the Eastâ€ Pada Interior Museum Nusa Tenggara Timur di Kupang - Gonzales, Celine Angelina (Intra, 2014)
Museum is a place that is used as a means of non-formal education and where preservation and recreation. Today, the museum has a problem on the level of security and reduced the number of visitors. Museum of East Nusa Tenggara is one museum that minimal level of security. The museum does not have a local image of the local area on the interior of the building. In addition the museum also less attractive to visitors. That requires re-design on the inside of the building so that the museum can fulfill a recreational values, informative, and educational preserfatif. Re-design is also expected to answer the security issues and presents the image in the local museum. The concept will be applied to the museum is a Journey to the East. This concept will be applied to each element of space and furniture. On the ceiling will be created artificial ceiling that feels like in the wild, then the material used on the floor is natural stone materials are sourced from the East. On walls and furniture will be applied to the formation of a stylized pentagon which symbolizes the protection of the people of the East. In the exhibition hall will be made a special diorama dioramas that tell the story of the formation of the East Nusa Tenggara trip, as well as telling the social life of the people of East Nusa Tenggara. the diorama is expected that the information presented can be easily understood visitors.